Los poderosos lo quieren todo - Guelbenzu, José María, 1944- ([Madrid] : Siruela, 2016)
Hermógenes Arbusto, a tax consultant and successful businessman, receives a visit from death one day in his office, and reacting quickly, manages to avoid the blow of the scythe, rushing out the door and leaving the reaper locked in behind him.
Online resource; title from ePub title page (Digitalia, viewed April 14, 2017)
Keywords: Death -- Fiction; Electronic books